When virtual violence has achieved us: education programs for cyberbullying excerpt and other virtual aggressions - Bozza, Thais Cristina Leite (2017)
This bibliographical research, as Art State, which had as main point to describe and analyze educational programs, which try to prevent and reduce cyber aggression. To begin, we would use data basis as Scielo Bvs, Eric, Apa Phyc Net and Bireme, to look for scientific articles published from 2000 to 2015; otherwise, selecting empiric studies, which contain enough information about the programs, we decided to stay with them, and we had not found enough studies only about what we wanted in the data basis. We also got about our researches in books, thesis, essays and websites. Finally, it is composed by 19 fonts, used to describe five educational programs: PRIRES, CYBERTRAINING, KIVA, CONRED AND BEATBULLYING. The programs were described from categories: objectives, theoretical references, characteristics, contain, activities and tests; and analyzed in the point of view of moral psychology from Piaget, looking to identify if the practical are positive to students’ development and moral self-regulation. The results indicate that the PRIRES program corresponding to our analysis criteria. We believe the importance of the present investigation, because we presented the characteristics from many faces of virtual aggression, also, we analyzed educational interventions presented in literature to prevent and decrease these kinds of problem, by bringing implications that could base future actions to Brazilian schools.